THE DEVELOPMENT OF VISUAL-BASED LEARNING RESOURCES IN ISLAMIC RELIGIOUS EDUCATION AT SCHOOL - Iskandar, Khusnan; Halim, Habib Abdul (JALIE: Journal of Applied Linguistics and Islamic Education, 2022)
The aim of this research and development was to produce a visual-based learning resource, namely a learning comic, which is practical, effective, engaging, and designed according to empirical needs analysis in the field. The product development was based on learning technology studies and the ADDIE model design framework. The result of this research and development was a learning comic equipped with practice questions to enhance students’ understanding of the material, visualized through images. The percentage of the evaluation/feedback from validators and field testing for the learning comic was 87.4%, meaning it was in the “very feasible” category (81% - 100%) on the Likert scale achievement conversion table. The analysis of the revised product concluded that: (1) The learning comic had been developed systematically and based on empirical needs analysis in the field; (2) The learning comic had met the feasibility criteria through the stages of development, analysis, and revision, making it suitable for use in the learning process to improve students’ understanding of Islamic Religious Education material at SMP Islam Sekaran Lamongan.